Challenges of energy investment in Nigeria : the proceedings of the international energy investment seminar organised by international energy services limited held in Lagos, Nigeria between 19th-21st April 1994 - Fawibe, Oladiran; International Energy Services Limited (Ibadan, Nigeria : Verity printers Limited, 1995)
The principles and platform of the challenges of Nigerian energy investment therefore lie between the potentials and benefits resulting from national investment programmes and the difficulties of enacting appropriate policies that would produce or actualize these programmes within a reasonable time.
Includes bibliographical references and index.
aia 7/9/16
Loans
Keywords: Energy development; Energy policy